Pengaruh Marketing Online, Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen Hotel Borobudur - Siska Widyawati; Ratih Puspitaningtyas Faeni (Reviu Akuntansi, Manajemen, dan Bisnis, 2021)
Purpose: This research aimed to examine the effect of marketing online, quality of service, and price on consumer satisfaction. Research Methodology: The population in this research was consumers who stay overnight at Hotel Borobudur Jakarta. The sample in this research was 100 consumer respondents at Hotel Borobudur Jakarta. The sample selection was made using the Probability Sampling method. How do distribute questionnaires with Random Sampling and search for sample using the Slovin Formula obtained the results of 100 respondents by distributing questionnaires to consumers at Hotel Borobudur Jakarta. The analytical tool used was SPSS v.20 software and Microsoft Excel 2007 assistance. Results: This research indicates that the marketing online, quality of service and price variables have a positive and significant effect on consumer satisfaction variables.